Cold Renal Ischemia: Comparison of Efficacy Between Two Techniques of Cooling, in a Swine Model - Guerra, Rodrigo; Leonardi, Eduardo Piotto; Otsuka, Rodrigo Arthur; Quitzan, Juliany; Kawano, Paulo Roberto [UNESP]; Yamamoto, Hamilto Akihissa [UNESP]; Amaro, João Luiz [UNESP]; Fugita, Oscar Eduardo Hidetoshi [UNESP] (Mary Ann Liebert, Inc., 2010)
Objectives: In a swine model of renal ischemia, we compared the effectiveness of the transureteral retrograde cold saline perfusion technique to the traditional method of renal cooling with ice slush, in achieving adequate parenchymal temperatures for functional preservation of the organ. Physiological and histological effects were also assessed.Methods: Twenty-four domestic male pigs were sampled into four groups to be submitted to a 60-minute ischemia of the left kidney without cooling, with either one of the two cooling techniques (cold saline retrograde perfusion or ice slush), or sham surgery. All of them had also a concomitant right nephrectomy. Renal cortical and medullary temperatures were recorded throughout the experiment. Urinary output was measured, and serum renal function tests were carried on, pre- and postoperatively. After 5 days, the animals were euthanized and their kidneys were submitted to histological analysis.Results: Mean renal temperature fell in both groups submitted to kidney cooling. With ice slush, a faster drop was observed and a lower minimum temperature was achieved (5.0 degrees C in the cortex and 6.3 degrees C in the medulla, vs. 25.4 degrees C and 24.9 degrees C with retrograde cooling). In the other groups, temperature was unchanged. Urinary output and serum creatinine worsened after the experiment, but without significant differences among groups. The histological analysis showed no differences among the four groups, for the studied ischemia time.Conclusions: Ice slush and retrograde perfusion of cold saline are both effective for cooling the kidney during ischemia. Ice slush is faster in doing so, and it allows much lower temperatures to be achieved in the renal parenchyma. With ischemia time of 60 minutes, no significant differences on the occurrence of functional and histological alterations were detected, even for the group without a cooling procedure.